Carbonaceous material suitable for negative electrode active material of capacitor devices, negative electrode for capacitor devices, capacitor device

KR103015418B1Active Publication Date: 2026-09-04KURARAY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237007493
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-15
Filing Date
2021-09-13
Publication Date
2026-09-04
Estimated Expiration
2041-09-13

Smart Images

  • Figure 112023024175817-PCT00001
    Figure 112023024175817-PCT00001
  • Figure 112023024175817-PCT00002
    Figure 112023024175817-PCT00002
  • Figure 112023024175817-PCT00003
    Figure 112023024175817-PCT00003
Patent Text Reader

Abstract

The present invention provides a carbonaceous material suitable for a negative electrode active material of a storage device (e.g., a lithium-ion secondary battery, a sodium-ion secondary battery, a lithium-sulfur battery, a lithium-air battery, an all-solid-state battery, a capacitor, etc.) having high discharge capacity and high cycle durability, a negative electrode comprising the carbonaceous material, and a storage device having the negative electrode. A carbonaceous material is disclosed having a nitrogen element content of 1.0 mass% or more and 4.0 mass% or less as determined by elemental analysis, an oxygen element content of 1.1 mass% or more and 2.1 mass% or less, and a carbon plane spacing (d002) observed by X-ray diffraction measurement of 3.70 Å or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] This patent application claims priority under the Paris Convention to Japanese Patent Application No. 2020-154229 (filing date: September 15, 2020), the entirety of which is accepted by reference herein.

[0002] The present invention relates to a carbonaceous material suitable for a negative electrode active material of a capacitor device, a negative electrode for a capacitor device comprising the carbonaceous material, and a capacitor device having the negative electrode. Background Technology

[0003] Non-aqueous electrolyte secondary batteries, such as lithium-ion secondary batteries, are widely used in small portable devices such as mobile phones and laptop computers because they have high energy density and excellent output characteristics. As a negative electrode material for lithium-ion secondary batteries, nitrogen-containing non-graphitizable carbon capable of doping (charging) and dedoping (discharging) of an amount of lithium exceeding the theoretical capacity of graphite, 372 mAh / g, has been disclosed (e.g., Patent Documents 1, 2, and 3). Prior art literature

[0004] Japanese Published Patent Application No. 2006-083012, International Publication No. 2019 / 009332, International Publication No. 2019 / 009333 The problem to be solved

[0005] Recently, as the application of lithium-ion rechargeable batteries to automotive applications is being considered, there is a growing demand for cycle durability in addition to the aforementioned high-capacity characteristics. For example, automotive lithium-ion rechargeable batteries are large and expensive, making replacement during use difficult. Therefore, lithium-ion rechargeable batteries are required to possess at least the same level of durability as automobiles, and in particular, high cycle durability is required so that discharge capacity does not drop even after repeated charging and discharging.

[0006] In this regard, the nitrogen element included in the carbon materials described in Patent Documents 1 to 3 can improve discharge capacity by becoming a lithium ion absorption site, but it can also become a reaction site with lithium ions, so there is a possibility that cycle durability cannot be secured, making it difficult to achieve both high discharge capacity and high cycle durability.

[0007] Accordingly, the present invention aims to provide a carbonaceous material suitable as a negative electrode active material for a storage device (e.g., a lithium-ion secondary battery, a sodium-ion secondary battery, a lithium-sulfur battery, a lithium-air battery, an all-solid-state battery, a capacitor, etc.) having high discharge capacity and high cycle durability, a negative electrode for a storage device including said carbonaceous material, and a storage device having said negative electrode. means of solving the problem

[0008] As a result of careful examination, the inventors discovered that the above problem can be solved by using a negative electrode made of a specific carbonaceous material, and thus arrived at the present invention.

[0009] That is, the present invention includes the following preferred embodiments.

[0010] [1] The nitrogen element content obtained by elemental analysis is 1.0 mass% or more and 4.0 mass% or less, and the oxygen element content is 1.1 mass% or more and 2.1 mass% or less, and also the carbon plane spacing (d) observed by X-ray diffraction measurement 002 Carbonaceous material with a thickness of 3.70 Å or more.

[0011] [2] A carbonaceous material described in [1] above, having an oxygen element content of 1.2 mass% or more and 2.0 mass% or less as determined by elemental analysis.

[0012] [3] Ratio of oxygen content to nitrogen content obtained by elemental analysis (R O / N A carbonaceous material described in [1] or [2] above, wherein ) is 0.30 or more and 1.0 or less.

[0013] [4] 1360 cm of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the peak's full width at half maximum in the vicinity is 250 cm -1 A carbonaceous material described in any one of the above [1] to [3].

[0014] [5] 1650 cm of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the peak's full width at half maximum in the vicinity is 98 cm -1 A carbonaceous material described in any one of the above [1] to [4].

[0015] [6] Average particle size D 50 A carbonaceous material described in any one of [1] to [5] above, having a thickness of 30 μm or less.

[0016] [7] A carbonaceous material derived from sugars, as described in any one of [1] to [6] above.

[0017] [8] A carbonaceous material described in any one of [1] to [7], used as a negative electrode active material for a capacitor device.

[0018] [9] A negative electrode for a capacitor device comprising the carbonaceous material described in [8] above.

[0019]

[10] A capacitor having a negative electrode for a capacitor device as described in [9] above. Effects of the invention

[0020] A capacitor device using a negative electrode comprising the carbonaceous material of the present invention has a high discharge capacity and high cycle durability. In addition, cycle durability in this specification refers to the capacity retention rate (cycle capacity retention rate) when the battery is used by repeatedly charging and discharging. Specific details for implementing the invention

[0021] Embodiments of the present invention will be described in detail below. Furthermore, the scope of the present invention is not limited to the embodiments described herein, and various modifications may be made within a scope that does not impede the spirit of the invention. In addition, the following description uses an example applied to a lithium-ion battery as a storage device.

[0022] In the carbonaceous material of the present invention, the nitrogen element content obtained by elemental analysis is 1.0 mass% or more. If the nitrogen element content in the carbonaceous material is less than 1.0 mass%, the number of sites for adsorbing and desorbing lithium ions during charging and discharging decreases, and the discharge capacity tends to decrease. In order to obtain such a high discharge capacity, the nitrogen element content in the carbonaceous material of the present invention needs to be 1.0 mass% or more, preferably 1.5 mass% or more, more preferably 1.75 mass% or more, and even more preferably 2.0 mass% or more.

[0023] In addition, in the carbonaceous material of the present invention, the nitrogen content obtained by elemental analysis is 4.0 mass% or less. If the nitrogen content in the carbonaceous material is greater than 4.0 mass%, the charge / discharge efficiency decreases. This is expected to be because nitrogen that was not accepted within the carbon framework exists as a surface functional group, such as a -NH2 group, and if the amount of such surface functional groups increases, it becomes impossible to suppress irreversible side reactions that may occur during charge / discharge.

[0024] In addition, it was found that when the nitrogen element content in the carbonaceous material is 4.0 mass% or less, a characteristic that the discharge capacity does not drop even when charging and discharging is repeated, that is, high cycle durability, tends to be obtained. Although the reason is not clear, the following reason can be considered. That is, if the nitrogen element is contained in large amounts in the carbonaceous material, it can be considered that a combination of factors occurs, such as a decrease in discharge capacity due to irreversible side reactions during the process of repeated charging and discharging, a decrease in discharge capacity accompanied by the expansion and contraction of the electrode during charging and discharging, and a decrease in discharge capacity due to structural changes around the nitrogen element, which is particularly deformed in the carbonaceous material, as a result of repeated charging and discharging. It can be considered that these factors that worsen cycle durability are eliminated by the nitrogen element content being 4.0 mass% or less.

[0025] In order to obtain such high cycle durability, the content of nitrogen element in the carbonaceous material needs to be 4.0 mass% or less, and in one embodiment, 3.8 mass% or less, preferably 3.5 mass% or less, more preferably 3.3 mass% or less, and even more preferably 3.0 mass% or less.

[0026] In addition, the details of the measurement of the nitrogen element content are as described below, and are measured by an elemental analysis method (inert gas dissolution method). The method of adjusting the nitrogen element content to the above range is not limited at all, but if the inert gas flow rate is made too large or the heating rate is made too small, the nitrogen element in the carbonaceous material is easily depleted, and the amount of nitrogen element in the carbonaceous material obtained is reduced, so it is advisable to adjust the inert gas flow rate, the heating rate, and the temperature of the heat treatment.

[0027] In the carbonaceous material of the present invention, the oxygen content obtained by elemental analysis is 1.1 mass% or more and 2.1 mass% or less. Since oxygen in the carbonaceous material, like nitrogen, acts as a site for adsorbing and desorbing lithium ions during charging and discharging, the discharge capacity tends to increase when the oxygen content is high. For this reason, the oxygen content obtained by elemental analysis needs to be 1.0 mass% or more, and in some embodiments, 1.1 mass% or more, and it is preferable to be 1.2 mass% or more, more preferable to be 1.4 mass% or more, even more preferable to be 1.5 mass% or more (1.5 mass% or more than 1.5 mass%), and even more preferable to be 1.6 mass% or more. On the other hand, when the oxygen content is high, it may cause a deterioration in cycle durability, similar to the nitrogen. For this reason, the oxygen element content in the carbonaceous material of the present invention is 2.0 mass% or less in one embodiment, preferably 1.9 mass% or less, and more preferably 1.8 mass% or less. The details of the measurement of the oxygen element content are as described in the examples, and are measured by the elemental analysis method (inert gas dissolution method) described below.

[0028] In the carbonaceous material of the present invention, the ratio R of the nitrogen element content to the hydrogen element content is used to obtain high discharge capacity and high cycle durability. N / H (Nitrogen element content / Hydrogen element content) is preferably 6 or more and 37 or less, more preferably 8 or more and 25 or less, even more preferably 10 or more and 20 or less, and even more preferably 12 or more and 15 or less. Furthermore, in the carbonaceous material of the present invention, in order to obtain high discharge capacity and high cycle durability, the ratio R of the oxygen element content to the nitrogen element content O / NIt is preferable that (oxygen element content / nitrogen element content) be between 0.30 and 1.0. This is believed to be due to the following reasons. That is, while increasing both the oxygen and nitrogen element content increases the discharge capacity, it deteriorates cycle durability. Furthermore, if either the oxygen or nitrogen element content is excessively high or low, the oxygen or nitrogen existing as surface functional groups, such as -OH groups or -NH2 groups, within the carbon structure increases, leading to a decrease in discharge capacity or cycle durability. To obtain both high discharge capacity and high cycle durability, R O / N The lower limit of is preferably 0.30 or higher, more preferably 0.35 or higher, and even more preferably 0.40 or higher. Also, R O / N The upper limit of is preferably 1.0 or less, more preferably 0.90 or less, and even more preferably 0.80 or less. R, the ratio of nitrogen element content to hydrogen element content. N / H R is derived from the nitrogen element content and hydrogen element content measured as above. N / H = Calculated by the formula nitrogen content / hydrogen content, and the ratio R of oxygen content to nitrogen content O / N R is derived from the oxygen element content and nitrogen element content measured as above. O / N It is calculated by the formula = Oxygen content / Nitrogen content.

[0029] In the carbonaceous material of the present invention, it is preferable that the lower the content of hydrogen elements in the carbonaceous material, the more the carbon edge portions are reduced and the carbon planes are widened, making electron movement easier. From this perspective, the content of hydrogen elements obtained by elemental analysis in the carbonaceous material is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and even more preferably 0.35 mass% or less. Furthermore, it is preferable that the higher the content of hydrogen elements in the carbonaceous material, the easier the adsorption and desorption of lithium ions becomes. From this perspective, the content of hydrogen elements in the carbonaceous material is preferably 0.10 mass% or more, and more preferably 0.15 mass% or more. The details of the measurement of the hydrogen element content are as described below, and are measured by an elemental analysis method (inert gas dissolution method).

[0030] In the carbonaceous material of the present invention, the carbon plane spacing (d) calculated by Bragg's equation from the peak position (diffraction angle 2θ) observed by powder X-ray diffraction is 002 ) is greater than or equal to 3.70 Å. d 002 For example, in cases where the carbon planes are closest, such as in graphite, it is about 3.35 to 3.40 Å, but d 002 As α becomes larger than in the case of graphite, lithium ions can move efficiently, and a high discharge capacity can be obtained by forming micropores capable of absorbing a large amount of clustered lithium. In this regard, d 002 It is necessary that is 3.70 Å or larger, preferably 3.74 Å or larger, and more preferably 3.76 Å or larger. Meanwhile, d 002 If is excessively large, the volume of the carbonaceous material increases, which may result in a decrease in the working capacity per volume. From this perspective, d 002 It is preferable that the value be 4.00 Å or less, more preferable that the value be 3.95 Å or less, and even more preferable that the value be 3.90 Å or less.

[0031] In the carbonaceous material of the present invention, the 1360 cm⁻¹ of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the full width at half maximum of the peak in the vicinity is 250 cm -1 It is desirable that it be greater than this. Here, 1360 cm -1 The peak in the vicinity is the Raman peak generally referred to as the D-band, and it is a peak attributed to structural disturbances and defects in the graphite. 1360 cm⁻¹ -1 The peak in the vicinity is typically 1345 cm. -1 ~ 1375 cm -1 , preferably 1350 cm -1 ~ 1370 cm -1 It is observed in the range. The full width at half maximum (FWHM) of the D-band peak is related to the amount of structural disturbance and defects in the graphite structure contained in the carbonaceous material. Such structural disturbance can be caused by the introduction of nitrogen elements into the carbon framework. The FWHM of the Raman peak in the D-band is 250 cm⁻¹. -1 If it is less than that, structural development proceeds excessively, and due to the development of the graphite structure, lithium ions tend to become unable to move in and out efficiently. Therefore, from the perspective of making it easier to lower resistance, 1360 cm -1 The full width at half maximum of the peak in the vicinity is preferably 250 cm -1 That is all, and more preferably 260 cm -1 That is all, and more preferably 270 cm -1 That is all. Also, the half-width is 300 cm. -1 If it is larger, it becomes difficult to maintain the graphite structure contained within the carbonaceous material, and the amorphous content increases, tending to reduce the number of sites capable of absorbing lithium. Consequently, the lithium ion absorption capacity decreases, which may lead to a reduction in discharge capacity. In this regard, 1360 cm -1 The full width at half maximum of the peak in the vicinity is preferably 300 cm -1 It is as follows.

[0032] In addition, in the carbonaceous material of the present invention, the 1650 cm⁻¹ of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the full width at half maximum of the peak in the vicinity is 98 cm -1 It is desirable that it be greater than this. Here, 1650 cm -1 The peak in this vicinity is the Raman peak generally referred to as the G-band, and it is a peak attributed to the graphite structure. The full width at half maximum of the Raman peak in the G-band is 98 cm. -1 If the range is below this, structural development proceeds excessively; due to the development of the graphite structure, lithium ions cannot efficiently enter or exit, and resistance tends to increase. Therefore, from the perspective of making it easier to lower resistance, 1650 cm -1 The full width at half maximum of the peak in the vicinity is preferably 98 cm -1 That is all, and more preferably 100 cm -1 That is all, and more preferably 102 cm -1 That is all. Also, 1650 cm -1 There is no specific limit on the upper limit of the peak's half-width in the vicinity, but it is typically 115 cm. -1 Less than, preferably 110 cm -1 Below, more preferably 107 cm -1 It is as follows.

[0033] Raman spectrum measurements are performed using a Raman spectrometer (e.g., the Horiba "LabRAM ARAMIS (VIS)" Raman spectrometer). Specifically, for example, the particle to be measured is set on the observation table stage, the objective lens magnification is set to 100x, and the focus is adjusted; while irradiating the measurement cell with 532 nm argon ion laser light, the exposure time is 1 second, the number of integrations is 100, and the measurement range is 50–2000 cm. -1 Measure by...

[0034] Average particle size D of the carbonaceous material of the present invention 50Since the particle size is 30 μm or less, in addition to improving the porosity during electrode fabrication, the free diffusion path of lithium ions within the carbonaceous material particles is reduced, making it easier to achieve rapid charging and discharging, which is desirable. Furthermore, in lithium-ion secondary batteries, it is important to increase the electrode area to improve input / output characteristics; to achieve this, it is necessary to reduce the coating thickness of the active material on the current collector plate during electrode preparation. From this perspective, the average particle size D 50 The smaller the value, the more desirable it is; preferably, it is 30 μm or less, more preferably 25 μm or less, even more preferably 20 μm or less, particularly preferably 18 μm or less, and most preferably 15 μm or less. When the average particle size of the carbonaceous material serving as the active material is below the above upper limit, it is easy to make the coating thickness thin during electrode preparation. In addition, the average particle size D of the carbonaceous material of the present invention 50 It is desirable that the particle size be 2 μm or larger, as this suppresses the increase in specific surface area and reactivity with the electrolyte caused by fine particles in the carbonaceous material, and makes it easier to suppress the increase in irreversible capacity. Furthermore, when manufacturing a negative electrode using a carbonaceous material, it is easy to secure voids formed between the carbonaceous materials, making it difficult to suppress the movement of lithium ions in the electrolyte, and making it easy to reduce the resistance of the capacitor device. From this perspective, the average particle size D 50 It is preferably 2 μm or more, more preferably 3 μm or more, more preferably 4 μm or more, and particularly preferably 5 μm or more. Average particle size D 50 The particle size at which the cumulative volume is 50% is obtained by measuring the particle size distribution using a laser scattering method with, for example, a particle size and particle size distribution measuring device ("MicroTrack MT3300EXII" manufactured by MicroTrack Bell Co., Ltd.).

[0035] The carbonaceous material of the present invention is,

[0036] (1) A process of mixing raw materials with a nitrogen-containing compound (hereinafter also referred to as "nitrogen-containing compound"),

[0037] (2) A process of heating the obtained mixture to a first predetermined temperature between 500 and 1200 ℃ in an inert gas atmosphere at a heating rate of 100 ℃ / hour or more,

[0038] (3) A process for obtaining a carbide by performing heat treatment in an inert gas, preferably in an inert gas atmosphere, at a temperature of 500 to 1200 ℃, preferably a first predetermined temperature, and

[0039] (4) A process of heating the obtained carbide in an inert gas atmosphere to a second predetermined temperature between the first predetermined temperature and 1400 ℃ at a heating rate of 100 ℃ / hour or more, and

[0040] (5) A process of performing heat treatment with an inert gas at a temperature of 800 to 1400 ℃, preferably at a second predetermined temperature.

[0041] It can be manufactured by a method including the above. In this specification, the above process (2) and / or (3) may be referred to as low-temperature firing (process), and the above process (4) and / or (5) may be referred to as high-temperature firing (process). The carbonaceous material can be obtained by conventional methods, for example, by grinding a carbide with a ball mill or a jet mill. Grinding may be performed after process (3) and / or after process (5).

[0042] There are no limitations on the raw materials for the carbonaceous material of the present invention, and known non-graphitizable carbonaceous raw materials such as petroleum pitch, coal pitch, and coconut shells may be applied. However, it is preferable to use sugars as a raw material that facilitates obtaining the carbonaceous material of the present invention having the above characteristics and facilitates modifying the structure, such as a cross-linked structure. By using sugars as raw materials, a carbonaceous material derived from sugars, more specifically derived from a substance having a sugar skeleton, can be obtained.

[0043] When sugars are used as raw materials, they are not particularly limited in type. Examples include monosaccharides such as glucose, galactose, mannose, fructose, ribose, and glucosamine; disaccharides such as sucrose, trehalose, maltose, cellobiose, maltitol, lactobionic acid, and lactosamine; and polysaccharides such as starch, glycogen, agarose, pectin, cellulose, chitin, and chitosan. These sugars may be used individually or in combination of two or more types. Among these sugars, starch is preferred because it is easy to obtain in large quantities. By using such sugars as raw materials, carbonaceous materials derived from sugars can be obtained.

[0044] Nitrogen-containing compounds are not particularly limited, but examples include inorganic ammonium salts such as ammonium chloride, ammonium sulfate, ammonium carbonate, and ammonium nitrate; organic ammonium salts such as ammonium formate, ammonium acetate, ammonium oxalate, and di-ammonium hydrogen citrate; aromatic amine hydrochlorides such as aniline hydrochloride and aminonaphthalene hydrochloride; and nitrogen-containing organic compounds such as melamine, pyrimidine, pyridine, pyrrole, imidazole, indole, and urea. Among these nitrogen-containing compounds, melamine and urea, which have a high nitrogen content within the molecule, are preferred from the perspective that the nitrogen element is easily absorbed into carbonaceous materials.

[0045] In addition, an acid catalyst may be added in addition to the above nitrogen-containing compound. The acid catalyst added is not particularly limited, but organic acids may be used as examples. Organic acids are not particularly limited, but examples include aliphatic carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanic acid, palmitic acid, stearic acid, succinic acid, linoleic acid, oleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, salicylic acid, phthalic acid, and terephthalic acid; hydroxycarboxylic acids such as lactic acid, tartaric acid, citric acid, and malic acid; carboxylic acids such as ethylenediamine-4-acetic acid; and sulfonic acids such as p-toluenesulfonic acid and methanesulfonic acid. By adding an acid catalyst, the reaction between sugars and nitrogen-containing compounds is promoted, and carbonaceous materials with a high nitrogen content tend to be obtained.

[0046] The mixing method of the raw material and the nitrogen-containing compound, or the raw material, the nitrogen-containing compound, and the acid catalyst, is not particularly limited, but dry or wet mixing may be used.

[0047] In the case of dry mixing, a mixture of a nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst, can be obtained by adding them to the raw material. In this case, from the perspective of uniformly mixing the nitrogen-containing compound, or the nitrogen-containing compound and the acid catalyst with the raw material, it is preferable to mix the nitrogen-containing compound, or the nitrogen-containing compound and the acid catalyst with the raw material in powder form by grinding them with a mortar and pestle or by grinding them with a ball mill.

[0048] In the case of wet mixing, for example, a solution may be prepared by dissolving the raw material in a solvent, and then mixing may be performed by adding a nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst, to this solution. Alternatively, mixing may be performed by spraying the solution onto the nitrogen-containing compound (e.g., spraying). Alternatively, mixing may be performed by adding the raw material to a solution prepared by dissolving the nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst, in a solvent. After mixing, the solvent may be evaporated if necessary. Through such treatment, a mixture of the raw material and the nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst, can be obtained. The solvent used is not particularly limited, but examples include water, alcohol solvents (ethanol, methanol, ethylene glycol, isopropyl alcohol, etc.), ester solvents (ethyl acetate, butyl acetate, ethyl lactate, etc.), ether solvents (tetrahydrofuran, dimethoxyethane, 1,4-dioxane, etc.), ketone solvents (acetone, 2-butanone, cyclopentanone, cyclohexanone, etc.), aliphatic hydrocarbon solvents (pentane, hexane, heptane, etc.), aromatic hydrocarbon solvents (toluene, xylene, mesitylene, etc.), nitrile solvents (acetonitrile, etc.), and chlorinated hydrocarbon solvents (dichloromethane, chloroform, chlorobenzene, etc.), and mixtures thereof. In order to uniformly mix the raw material and the nitrogen-containing compound, or the raw material, the nitrogen-containing compound, and the acid catalyst, it is effective for both to be easily soluble in the solvent, so water, alcohol solvents, and mixtures thereof are preferred as solvents. The method of evaporating the solvent is not particularly limited, but examples include heat treatment, reduced pressure treatment, and a combination thereof. The temperature of the heat treatment should be a temperature at which thermal decomposition of nitrogen-containing compounds is unlikely to occur, or at which thermal decomposition of sugars is unlikely to occur, and varies depending on the type of solvent, but is preferably 40 to 150°C, more preferably 50 to 120°C, and even more preferably 60 to 100°C.

[0049] The amount of nitrogen contained in the nitrogen-containing compound mixed with the raw material is, with respect to the mass of the resulting mixture, preferably 0.1 molar equivalent or more, more preferably 0.2 molar equivalent or more, even more preferably 0.3 molar equivalent or more, preferably 2.0 molar equivalent or less, more preferably 1.0 molar equivalent or less, and even more preferably 0.8 molar equivalent or less. It is desirable for the amount of the nitrogen-containing compound mixed to be above the lower limit, as nitrogen elements are efficiently absorbed into the resulting carbonaceous material. If the amount of the nitrogen-containing compound mixed to be below the upper limit, the introduction of excess nitrogen elements can be suppressed and excessive disruption of the carbon structure is not caused, so it becomes easier for the capacitor device containing the resulting carbonaceous material to exhibit high discharge capacity and also high cycle durability.

[0050] In the manufacturing method of the present invention, a mixture obtained from a process (1) of mixing raw materials with a nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst is heated to perform a first calcination, and a second calcination is performed on the obtained carbonized material.

[0051] In the first firing, preferably, the mixture obtained from process (1) is heated to a temperature between 500 and 1200°C, preferably between 600 and 1150°C, more preferably between 700 and 1100°C, and even more preferably between 800 and 1100°C, preferably at the first predetermined temperature described below, and heat treatment is performed in an inert gas, preferably in an inert gas atmosphere, to obtain a carbide [process (3)]. For example, nitrogen gas may be used as an inert gas. The temperature at which heat treatment is performed with an inert gas is preferably the first predetermined temperature below, but is not particularly limited as long as it is within the above range. Also, the temperature at which heat treatment is performed with an inert gas may be a constant temperature, but is not particularly limited as long as it is within the above range.

[0052] At this time, the mixture obtained from process (1), which mixes the raw material with a nitrogen-containing compound, or a nitrogen-containing compound and an acid catalyst, is preferably heated to a first predetermined temperature between 500 and 1200°C, preferably between 600 and 1150°C, more preferably between 700 and 1130°C, and even more preferably between 800 and 1100°C, at a heating rate of 100°C / hour or more, preferably between 100 and 600°C / hour, in an inert gas atmosphere such as nitrogen gas [process (2)]. The heating in process (2) is carried out in an inert gas atmosphere, but the heat treatment may be carried out under an inert gas supply.

[0053] In the manufacturing method of the present invention, a second calcination is performed on the carbide obtained by the first calcination. In the second calcination, preferably, the carbide obtained from process (3) is heated and heat treatment is performed in an inert gas atmosphere, preferably an inert gas atmosphere such as nitrogen gas, at a temperature between 800 to 1400 ℃, preferably 1050 to 1380 ℃, more preferably 1100 to 1370 ℃, even more preferably 1150 to 1360 ℃, and particularly preferably 1200 to 1350 ℃, preferably at the second predetermined temperature described below [Process (5)]. The temperature at which heat treatment is performed with an inert gas is preferably the second predetermined temperature below, but is not particularly limited as long as it is within the above range. Also, the temperature at which heat treatment is performed with an inert gas may be a constant temperature, but is not particularly limited as long as it is within the above range.

[0054] At this time, a volatile organic material may be added to the carbonized material obtained from process (3) and provided to process (4). Volatile organic material refers to an organic compound that does not carbonize (e.g., 80% or more, preferably 90% or more) and volatilizes (gases or decomposes by thermal decomposition) when heat-treated with an inert gas such as nitrogen (e.g., 500°C or higher). Volatile organic material is not particularly limited, but examples include thermoplastic resins and low-molecular-weight organic compounds. Specifically, thermoplastic resins include polystyrene, polyethylene, polypropylene, poly(meth)acrylic acid, poly(meth)acrylic acid esters, etc. Also, in this specification, (meth)acrylic is a general term for methacrylic and acrylic. Examples of low molecular weight organic compounds include toluene, xylene, mesethylene, styrene, naphthalene, phenanthrene, anthracene, and pyrene. Polystyrene, polyethylene, and polypropylene are preferred as thermoplastic resins, as it is desirable that they volatilize at the calcination temperature and do not oxidize or reactivate the surface of the carbon precursor upon thermal decomposition. Regarding low molecular weight organic compounds, it is also desirable that they have low volatility at room temperature (e.g., 20°C) from a safety perspective, and naphthalene, phenanthrene, anthracene, and pyrene are preferred. Adding such volatile organic compounds is desirable in that it allows for a smaller specific surface area while maintaining the characteristic structure of the carbonaceous material of the present invention.

[0055] At this time, the carbide obtained from process (3) is preferably heated to a second predetermined temperature in the range of a first predetermined temperature to 1400°C at a heating rate of 100°C / hour or more, preferably 100°C to 600°C / hour, in an inert gas atmosphere such as nitrogen gas [process (4)]. The heating in process (4) is carried out in an inert gas atmosphere, but the heat treatment may be carried out under an inert gas supply.

[0056] The second firing is typically carried out at a temperature higher than the temperature of the first firing, preferably at a temperature higher than the temperature of the first firing. For this reason, in this specification, the first firing and the second firing may be referred to as low-temperature firing and high-temperature firing, respectively. The temperature of the second firing, i.e., the second predetermined temperature in process (4), is preferably a temperature higher than the temperature of the first firing, i.e., the first predetermined temperature in process (2), in order to obtain a carbonaceous material that provides high discharge capacity and charge / discharge efficiency when used as an electrode. The second predetermined temperature is more preferably a temperature 50 to 700 ℃ higher than the first predetermined temperature, even more preferably a temperature 100 to 500 ℃ higher than the first predetermined temperature, even more preferably a temperature 150 to 400 ℃ higher than the first predetermined temperature, and particularly preferably a temperature 200 to 300 ℃ higher than the first predetermined temperature. In addition, the second predetermined temperature is preferably 1400 ℃ or lower, more preferably 1380 ℃ or lower, even more preferably 1360 ℃ or lower, and particularly preferably 1350 ℃ or lower.

[0057] The carbonaceous material of the present invention can preferably be used as a negative electrode active material for a capacitor device. The present invention also provides a negative electrode for a capacitor device comprising the carbonaceous material of the present invention.

[0058] In the following, a method for manufacturing a negative electrode for a capacitor device according to the present invention is described in detail. The negative electrode according to the present invention can be manufactured by adding a binder to a carbonaceous material according to the present invention, adding and mixing a suitable amount of a suitable solvent to form an electrode mixture, then applying it to a current collector plate made of a metal plate or the like, drying it, and then pressurizing it.

[0059] In addition, lithium predoff may be performed by a known method for the purpose of reducing the irreversible capacity of the obtained negative electrode.

[0060] By using the carbonaceous material of the present invention, an electrode (negative electrode) having high conductivity can be manufactured without adding a conductivity aid, but for the purpose of imparting higher conductivity, a conductivity aid may be added when preparing the electrode mixture as necessary. Conductive carbon black, vapor-grown carbon fiber (VGCF), nanotubes, etc., may be used as conductivity aids. The amount of conductivity aid added varies depending on the type of conductivity aid used, but if the amount added is too small, the expected conductivity may not be obtained, and if it is too large, the dispersion in the electrode mixture may be poor. In this regard, the preferred ratio of the conductivity aid added is 0.5 to 10 mass% (where the amount of active material (carbonaceous material) + amount of binder + amount of conductivity aid = 100 mass%), more preferably 0.5 to 7 mass%, and particularly preferably 0.5 to 5 mass%. As for the binder, it is not particularly limited as long as it does not react with the electrolyte, such as PVDF (polyvinylidene fluoride), polytetrafluoroethylene, and a mixture of SBR (styrene-butadiene rubber) and CMC (carboxymethylcellulose). Among these, PVDF is preferred because the PVDF attached to the surface of the active material rarely inhibits lithium ion movement, thereby obtaining good input / output characteristics. To dissolve PVDF and form a slurry, a polar solvent such as N-methylpyrrolidone (NMP) is preferably used, but an aqueous emulsion such as SBR or CMC dissolved in water may also be used. If the amount of binder added is excessively large, the resistance of the resulting electrode increases, which may increase the internal resistance of the battery and degrade battery performance. Furthermore, if the amount of binder added is excessively small, the bonding between particles of the negative electrode material and with the current collector may become insufficient.The preferred amount of binder added varies depending on the type of binder used, but for example, in the case of PVDF-based binders, it is preferably 3 to 13 mass%, and more preferably 3 to 10 mass%. On the other hand, in the case of binders using water as a solvent, multiple binders are often mixed and used, such as a mixture of SBR and CMC, and as the total amount of all binders used, it is preferable to have 0.5 to 5 mass%, and more preferably 1 to 4 mass%. In addition, the carbonaceous material of the present invention in the electrode composite is preferably 80 mass% or more, and more preferably 90 mass% or more.

[0061] In addition, the carbonaceous material of the present invention in the electrode mixture is preferably 100 mass% or less, and more preferably 97 mass% or less.

[0062] The electrode active material layer is basically formed on both sides of the current collector plate, but may be formed on one side if necessary. The thicker the electrode active material layer, the more desirable it is for increasing capacitance. However, since a larger electrode surface area facing the counter electrode is advantageous for improving input / output characteristics, if the electrode active material layer is excessively thick, the input / output characteristics may deteriorate. From the perspective of achieving both high capacitance and input / output characteristics, the thickness of the active material layer (per side) is preferably 10 to 80 μm, more preferably 20 to 75 μm, and even more preferably 30 to 75 μm.

[0063] The capacitor device of the present invention includes a negative electrode for the capacitor device of the present invention. The capacitor device having a negative electrode for the capacitor device comprising a carbonaceous material of the present invention has a high discharge capacity and high cycle durability.

[0064] When forming a negative electrode for a capacitor device using the carbonaceous material of the present invention, other materials constituting the battery, such as the positive electrode material, separator, and electrolyte, are not particularly limited, and various materials conventionally used or proposed for non-aqueous solvent secondary batteries can be used.

[0065] For example, as a positive electrode material, layered oxide systems (represented as LiMO2, where M is a metal: e.g., LiCoO2, LiNiO2, LiMnO2, or LiNi x Co y Mo z Composite metal chalcogen compounds such as O2 (where x, y, and z represent composition ratios), olivine-based (represented as LiMPO4, where M is a metal: e.g., LiFePO4, etc.), and spinel-based (represented as LiM2O4, where M is a metal: e.g., LiMn2O4, etc.) are preferred, and these chalcogen compounds may be mixed and used as needed. A positive electrode is formed by molding these positive electrode materials together with a suitable binder and a carbon material for imparting conductivity to the electrode, thereby forming a layer on a conductive current collector.

[0066] The non-aqueous solvent type electrolyte used in combination with these positive and negative electrodes is generally formed by dissolving an electrolyte in a non-aqueous solvent. As the non-aqueous solvent, one or more organic solvents such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, dimethoxyethane, diethoxyethane, γ-butyllactone, tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, or 1,3-dioxolane may be used. Additionally, as the electrolyte, LiClO4, LiPF6, LiBF4, LiCF3SO3, LiAsF6, LiCl, LiBr, LiB(C6H5)4, or LiN(SO3CF3)2 are used.

[0067] A storage device is generally formed by arranging the positive and negative electrodes formed as described above in opposition with a permeable separator interposed as necessary, and immersing them in an electrolyte. As such a separator, a permeable or permeable separator made of nonwoven fabric or other porous materials commonly used in secondary batteries may be used. Alternatively, a solid electrolyte made of a polymer gel impregnated with an electrolyte may be used instead of, or together with, a separator.

[0068] The carbonaceous material of the present invention is preferably a carbonaceous material for a battery (typically a storage device for vehicle drive) mounted in a vehicle, such as an automobile. In the present invention, the vehicle is not particularly limited and may be a vehicle known as an electric vehicle, or a hybrid vehicle with a fuel cell or internal combustion engine, but at least comprises a power supply unit equipped with the above-mentioned battery, an electric drive mechanism driven by power supply from the power supply unit, and a control device for controlling the same. The vehicle may further be equipped with a generator brake or a regenerative brake, and may be equipped with a mechanism that converts energy from braking into electricity and charges the above-mentioned storage device.

[0069] Examples

[0070] The present invention will be specifically described below by way of examples, but these do not limit the scope of the present invention. Additionally, a method for measuring physical property values ​​of carbonaceous materials is described below; however, the physical property values ​​described in this specification, including the examples, are based on values ​​obtained by the following method.

[0071] (Elemental Analysis)

[0072] Elemental analysis was performed based on the inert gas dissolution method using the oxygen, nitrogen, and hydrogen analyzer EMGA-930 manufactured by Horiba Corporation.

[0073] The detection method of the device in question is,

[0074] Oxygen: Inert gas melting-non-dispersive infrared absorption (NDIR),

[0075] Nitrogen: Inert Gas Melt-Heat Conduction (TCD),

[0076] Hydrogen: Inert Gas Melt-Non-Dispersive Infrared Absorption (NDIR)

[0077] Calibration was performed using (oxygen·nitrogen) Ni capsules, TiH2 (H standard sample), and SS-3 (N, O standard sample). As a pretreatment, 20 mg of a sample with a measured moisture content at 250°C for about 10 minutes was placed in a Ni capsule, and after degassing for 30 seconds in an elemental analysis apparatus, the sample was measured.

[0078] The test was analyzed using 3 samples, and the average value was used as the analysis value.

[0079] (X-ray diffraction)

[0080] Carbonaceous material powder was loaded into a sample holder, and X-ray diffraction measurements were performed using a MiniFlex II manufactured by Rigaku. CuKα (λ = 1.5418 Å) was used as the source, and the scanning range was set to 10° < 2θ < 35°.

[0081] (Raman spectrum)

[0082] Using a Raman spectrometer ("LabRAM ARAMIS (VIS)" manufactured by Horiba, Ltd.), the target particles, which are carbonaceous materials, were set on the observation stage, the objective lens magnification was set to 100x, the focus was set, and measurements were taken while irradiating with argon ion laser light. The details of the measurement conditions are as follows.

[0083] Wavelength of argon ion laser light: 532 nm

[0084] Laser power on sample: 15 mW

[0085] Resolution: 5 - 7 cm -1

[0086] Measurement range: 50 - 2000 cm -1

[0087] Exposure time: 1 second

[0088] Accumulated count: 100 times

[0089] Peak Intensity Measurement: Baseline Correction Polynom - 3rd-order automatic correction

[0090] Peak Search & Fitting Process GaussLoren

[0091] (Average particle size D by laser scattering method 50 )

[0092] The average particle size (particle size distribution) of the carbonaceous material was measured by the following method. The sample was placed in an aqueous solution containing 5 mass% of a surfactant ("Toriton X100" manufactured by Wako Pure Chemical Industry Co., Ltd.), treated with an ultrasonic cleaner for at least 10 minutes, and dispersed in the aqueous solution. The particle size distribution was measured using this dispersion. The particle size distribution measurement was performed using a particle size and distribution measuring device ("MicroTrac MT3300EXII" manufactured by MicroTrac Bell Co., Ltd.). D 50 The particle size at which the cumulative volume becomes 50% is used as the average particle size.

[0093] (Example 1)

[0094] 10 g of starch, 0.29 g of melamine (0.037 mol per 1 mol of starch monosaccharide unit), and 0.76 g of adipic acid (0.084 mol per 1 mol of starch monosaccharide unit) were placed in a 100 ml container and mixed by shaking at 2 Hz for 5 minutes. The resulting mixture was heated to 600 ℃ under a nitrogen gas atmosphere. At this time, the heating rate to 600 ℃ was set to 600 ℃ / hour (10 ℃ / min). Subsequently, a carbonization treatment was performed by heat treatment (low-temperature calcination) at 600 ℃ for 60 minutes under a nitrogen gas stream to obtain a carbide (first calcination). At this time, the nitrogen gas supply rate was 1 L / min per 10 g of starch. Afterward, the obtained carbide was ground using a ball mill to obtain a ground carbide. Next, a carbonaceous material was obtained by performing a high-temperature sintering treatment on the crushed carbide by raising the temperature to 1000 ℃ and heat-treating it at 1000 ℃ for 60 minutes (second sintering). At this time, the heating rate to 1000 ℃ was set to 600 ℃ / hour (10 ℃ / min). The above heating and heat treatment were carried out under a nitrogen gas stream. The supply amount of nitrogen gas was 3 L / min per 5 g of crushed carbide.

[0095] (Example 2)

[0096] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that melamine was 0.045 mol per 1 mol of starch monosaccharide unit and adipic acid was 0.025 mol per 1 mol of starch monosaccharide unit.

[0097] (Example 3)

[0098] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that melamine was 0.075 mol per 1 mol of starch monosaccharide unit and adipic acid was 0.042 mol per 1 mol of starch monosaccharide unit, and the second calcination temperature was 1100 ℃.

[0099] (Example 4)

[0100] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that melamine was set to 0.15 moles per 1 mole of starch monosaccharide unit and the second calcination temperature was set to 1100 ℃.

[0101] (Example 5)

[0102] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that melamine was 0.045 mol per 1 mol of starch monosaccharide unit and adipic acid was 0.042 mol per 1 mol of starch monosaccharide unit.

[0103] (Comparative Example 1)

[0104] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that the melamine was 0.15 moles per 1 mole of starch monosaccharide unit.

[0105] (Comparative Example 2)

[0106] A carbonaceous material was obtained by performing the same treatment as Comparative Example 1, except that the second firing temperature was set to 1200 ℃.

[0107] (Comparative Example 3)

[0108] A carbonaceous material was obtained by performing the same treatment as Comparative Example 1, except that the second firing temperature was set to 800 ℃.

[0109] (Comparative Example 4)

[0110] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that the mixture of Example 1 was made into starch.

[0111] (Comparative Example 5)

[0112] Glucose and ammonium chloride (1.1 mol per 1 mol of glucose) were mixed in a mortar and pestle. The resulting mixture was heated to 1000 °C in a nitrogen gas atmosphere. At this time, the heating rate to 1000 °C was set to 240 °C / hour (4 °C / min). Subsequently, a carbonization treatment was performed by heat treatment at 1000 °C for 60 minutes under a nitrogen gas stream to obtain a carbide (1st calcination). At this time, the nitrogen gas supply amount was 1 L / min per 5 g of glucose. Afterward, the obtained carbide was ground using a ball mill to obtain a ground carbide. Next, the ground carbide was heated to 1200 °C and heat treatment was performed at 1200 °C for 60 minutes to obtain a carbonaceous material (2nd calcination). At this time, the heating rate to 1200 ℃ was set to 600 ℃ / hour (10 ℃ / min). The heating and heat treatment were carried out under a nitrogen gas stream. The nitrogen gas supply amount was 3 L / min per 5 g of crushed carbide.

[0113] (Comparative Example 6)

[0114] A carbonaceous material was obtained by performing the same treatment as in Example 1, except that the amount of melamine was 0.015 moles per 1 mole of starch monosaccharide unit and the second calcination temperature was 800 ℃.

[0115] (Fabrication of electrodes)

[0116] Using the carbonaceous materials obtained in each example and each comparative example, the negative electrode was fabricated in the following order.

[0117] 95 parts by mass of a carbonaceous material, 2 parts by mass of conductive carbon black (TIMICAL “Super-P” (registered trademark)), 1 part by mass of CMC, 2 parts by mass of SBR, and 90 parts by mass of water were mixed to obtain a slurry. The obtained slurry was applied to a copper foil with a thickness of 18 μm, dried, and then pressed to obtain an electrode with a thickness of 45 μm.

[0118] (Initial battery capacity and charge / discharge efficiency)

[0119] The electrode fabricated above was used as the working electrode, and metallic lithium was used as the counter electrode and reference electrode. Propylene carbonate and ethylene glycol dimethyl ether were mixed in a volume ratio of 1:1 and used as solvents. LiClO4 was dissolved at 1 mol / L in this solvent and used as the electrolyte. A polypropylene membrane was used as the separator. A coin cell was fabricated in a glove box under an argon atmosphere.

[0120] For the lithium secondary battery of the above configuration, a charge-discharge test was performed using a charge-discharge test device (manufactured by Toyo System Co., Ltd., "TOSCAT") after measuring the DC resistance value before initial charging. Lithium doping was carried out at a rate of 70 mA / g relative to the mass of the active material until the lithium potential reached 1 mV. Additionally, a constant voltage of 1 mV relative to the lithium potential was applied for 8 hours, and doping was terminated. The capacity at this time (mAh / g) was defined as the charge capacity (initial charge capacity) (evaluation of initial charge). Subsequently, dedoping was carried out at a rate of 70 mA / g relative to the mass of the active material until the lithium potential reached 1.5 V, and the discharged capacity at this time was defined as the discharge capacity (initial discharge capacity) (evaluation of initial discharge). The ratio of discharge capacity to charge capacity was set as the charge-discharge efficiency (initial charge-discharge efficiency) and as an indicator of the utilization efficiency of lithium ions within the battery.

[0121] <Cycle Capacity Retention Rate>

[0122] The discharge capacity obtained after repeating the above initial charge / discharge evaluation conditions 10 times was set as the discharge capacity of the 10th cycle. In addition, the 10-cycle capacity retention rate was calculated by the following formula.

[0123] 10-Cycle Capacity Retention Rate (%) = Discharge Capacity at 10th Cycle (mAh / g) / Initial Discharge Capacity (mAh / g) × 100

[0124] The manufacturing conditions of the carbonaceous material in each example and each comparative example, the evaluation results of the physical properties of the obtained carbonaceous material, and the evaluation results of the battery characteristics are each shown in the following tables.

[0125] The batteries fabricated using the carbonaceous materials of each example exhibited a high discharge capacity along with a high cycle capacity retention rate. On the other hand, the batteries fabricated using the carbonaceous materials of each comparative example, which did not have a predetermined nitrogen or oxygen content, did not have a sufficiently high discharge capacity or cycle capacity retention rate.

[0126]

[0127]

[0128]

[0129]

Claims

Claim 1 The nitrogen element content obtained by elemental analysis is 1.0 mass% or more and 3.49 mass% or less, the oxygen element content is 1.1 mass% or more and 2.1 mass% or less, the hydrogen element content is greater than 0.10 mass% and 0.50 mass% or less, and the ratio R of the nitrogen element content to the hydrogen element content N / H (Nitrogen elemental content / Hydrogen elemental content) is 6 or greater and less than 34.9, and additionally, the carbon plane spacing (d) observed by X-ray diffraction measurement 002 Carbonaceous material with a thickness of 3.70 Å or more. Claim 2 A carbonaceous material according to claim 1, wherein the oxygen element content obtained by elemental analysis is 1.2 mass% or more and 2.0 mass% or less. Claim 3 In claim 1, the ratio of oxygen content to nitrogen content obtained by elemental analysis (R O / N Carbonaceous material having a value of 0.32 or higher and 1.0 or lower. Claim 4 In claim 1, the 1360 cm⁻¹ of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the peak's full width at half maximum in the vicinity is 250 cm -1 Lee Sang-in, carbonaceous material. Claim 5 In claim 1, the 1650 cm⁻¹ of the Raman spectrum observed by laser Raman spectroscopy -1 The value of the peak's full width at half maximum in the vicinity is 98 cm -1 Lee Sang-in, carbonaceous material. Claim 6 In claim 1, average particle size D 50 A carbonaceous material with a thickness of 30 μm or less. Claim 7 In claim 1, the carbonaceous material is derived from sugars. Claim 8 A carbonaceous material for use as a negative electrode active material of a capacitor device, in any one of claims 1 to 7. Claim 9 A negative electrode for a capacitor device comprising the carbonaceous material described in claim 8. Claim 10 A capacitor having a negative electrode for a capacitor device as described in claim 9.

Citation Information

Patent Citations

  • Carbonaceous material for negative electrode active material of non-aqueous electrolyte secondary battery, negative electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery and method for producing carbonaceous material

    KR1020200024783A